Longitudinal Associations Between Household Solid Fuel Use and Handgrip Strength in Middle-Aged and Older Chinese Individuals: The China Health and Retirement Longitudinal Study - Yashu Liu; Qing Chang; Yang Xia; Yuhong Zhao (Frontiers Media S.A., 2022)
BackgroundHousehold solid fuel have been associated with changes of handgrip strength (HGS). However, no study has explored the longitudinal associations between household solid fuel use and HGS. Thus, the aim of our cohort study was to investigate the longitudinal associations between household fuel use and HGS.MethodsThe study was based on the China Health and Retirement Longitudinal Study. A handheld dynamometer was used to measure HGS. Household fuel use statuses were collected using questionnaires. Analyses of covariance were performed to examine the associations between household fuel use and HGS.ResultsThe study included 9,382 participants during a 4-year follow-up. The participants who used solid fuel for cooking had more decreases of HGS than those who used clean fuel (P < 0.0001). The least square means (95% CIs) of changes of HGS for participants who used solid fuel and those who used clean fuel for cooking were −1.67 (−2.15, −1.19) and−2.27 (−2.75, −1.79), respectively. The association between fuel use for heating and HGS was non-significant (P = 0.63). The interaction terms of sex to cooking fuel (P = 0.04) and smoking to cooking fuel (P < 0.001) were significant; men and participants who had ever smoked had higher decreases in HGS.ConclusionUsing household solid fuel for cooking but not heating was associated with more decreases in HGS. Proper ventilation and clean fuel should be promoted for public health.